STRATEGY FOR DEVELOPING NATURAL ATTRACTIONS BY THE TOURISM OFFICE IN BENER MERIAH REGENCY, ACEH PROVINCE - Irwandi Irwandi; Wirman Syafri; Faria Ruhana (Sean Institute, 2023)
This study aims to determine the development of natural attractions in BenerMeriah district, Aceh province. The research method used in this study is qualitative. In this study, based on his analysis, the author of the descriptive method by combining it with qualitative methods. The results of this study state that the development of natural attractions by the Tourism Office in BenerMeriah Regency is considered to be quite good because development has been carried out by improving access and also attractions in natural attractions, but it has not been carried out optimally, because based on reality it is still not effective in the development carried out, it is also proven that the number of tourist visits and regional original opinions is still low in 2019-2021. Strategies carried out by the tourism office include prioritizing the development of natural attractions by utilizing the potential and increasing the development of infrastructure, facilities, and infrastructure according to the needs of visiting tourists. And optimizing cooperation with stakeholders in developing natural attractions in Bener Meriah Regency and increasing attractiveness and being more active in promoting natural attractions in BenerMeriah Regency, Aceh Province.